SELF-REGULATED LEARNING DAN DUKUNGAN ORANG TUA DALAM MEMPREDIKSI KETEPATAN PENYELESAIAN SKRIPSI MAHASISWA - Nugroho, Adi; Permana, Hinggil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of Self-Regulated Learning (SRL) and parental support on the timeliness of thesis completion among students of the Islamic Education Management Study Program at Universitas Singaperbangsa Karawang. This research employed a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to 122 final-year students selected using purposive sampling techniques. The findings revealed that Self-Regulated Learning and parental support partially and simultaneously had a significant effect on thesis completion timeliness. Self-Regulated Learning was found to be the dominant predictor compared to parental support. The regression equation obtained was Y = 6.123 + 0.511X1 + 0.311X2. These findings indicate that students with strong self-regulation abilities and adequate parental support tend to complete their thesis more effectively and on time.